Virginia Women : Their Lives and Times - Kierner, Cynthia A., 1958-; Treadway, Sandra Gioia (Book collections on Project MUSE., 2014)
Virginia Women is the first of two volumes exploring the history of Virginia women through the lives of exemplary and remarkable individuals. This collection of seventeen essays, written by established and emerging scholars, recovers the stories and voices of a diverse group of women, from the seventeenth century through the Civil War era. Placing their subjects in their larger historical contexts, the authors show how the experiences of Virginia women varied by race, class, age, and marital status, and also across both space and time. Some essays examine the lives of wellknown women-such as F.